2007
DOI: 10.1086/519866
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Bioaerosol Contamination With Aspergillus Species Before and After Cleaning in Rooms Filtered With High-Efficiency Particulate Air Filters That House Patients With Hematologic Malignancy

Abstract: Concentration of bioaerosol contamination with Aspergillus species was increased in rooms sampled 1 hour after cleaning compared with rooms sampled before cleaning, suggesting a possible correlation between re-entrained bioaerosols (ie, those suspended by activity in the room) after cleaning and the risk of nosocomial invasive aspergillosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 7 publications
0
11
0
1
Order By: Relevance
“…Similarly, other studies have concluded that humidity was the main parameter affecting the bioaerosol concentrations in hospital lobbies and cleaning rooms (Ekhaise et al, 2008; Lee et al, 2007; Park et al, 2013). Moreover, a previous study demonstrated that airborne contamination was higher in old versus new ORs, which is consistent with the results of this work (Audurier et al, 1985).…”
Section: Discussionmentioning
confidence: 68%
“…Similarly, other studies have concluded that humidity was the main parameter affecting the bioaerosol concentrations in hospital lobbies and cleaning rooms (Ekhaise et al, 2008; Lee et al, 2007; Park et al, 2013). Moreover, a previous study demonstrated that airborne contamination was higher in old versus new ORs, which is consistent with the results of this work (Audurier et al, 1985).…”
Section: Discussionmentioning
confidence: 68%
“…This can be attributed to type of service offered in each particular hospital. Among the reasons for increased density of microorganisms in some hospitals are commuting and crowd inside the ward as well as the type of services and hospitalized patients in the hospital (24,25). Bahonar hospital, is an old hospital that hosts patients with trauma (impact), the number of visitors is larger than other hospital, thus it is regarded as a busy place.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is good evidence for increases in the level of Aspergillus conidia during structural work, both inside and in the vicinity of hospitals. The mean concentration of fungi of the Aspergillus genus within hospitals varies between 3 and 105 CFU/m 3 , according to the studies reviewed [49,54,92–95]. Curtis et al.…”
Section: Special and Additional Preventive Measuresmentioning
confidence: 99%